Structure and Symmetrization of Hydrogen Bonding in Ices VIII and X at High Pressure: A Density Functional Theory Approach - Pantha, Nurapati; Adhikari, Narayan Prasad (Journal of Institute of Science and Technology, 2015)
We study the change in structural properties of ice by taking initial structure of “ice VIII”, with space group symmetry I41/amd, as a function of elevating pressure up to 120 GPa in density-functional theory (DFT) level of calculations implemented by Quantum ESPRESSO package. Consistent with the standard laws of thermodynamics, our calculations show that the physical size (volume and cell parameters) of the unit cell compresses monotonically on increasing pressure. We also compare our DFT results of these parameters with the available experimental values performed at finite temperature. The comparison shows good agreement between the quantities, within 5%, with slightly higher experimental values. At 100 GPa of pressure, hydrogen atom comes exactly at the midpoint of two boneded oxygens, called hydrogen-bonded symmetrization, which at low pressure remains nearby one of the oxygens. This symmmetrized structure is characterized by a new phase of the system known as “ice X” and the boundary pressure, 100 GPa, defines the transition pressure (P0) for changing phase from “ice VIII” to “ice X”. The transition pressure (P0) of the present work agrees well within 2% of previously reported results. Journal of Institute of Science and Technology, 2014, 19(2): 14-19 Journal of Institute of Science and Technology, 2014, 19(2): 14-18